Perancangan Aplikasi Pencatatan Persediaan Apotek Berbasis Website - Hetika Hetika; Fitri Amaliyah; Yeni Priatna Sari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Merchandise inventory is a crucial asset for trading companies, including pharmacies operating in the healthcare sector. During the Covid-19 pandemic, demand for medicines, supplements, and medical devices has increased, strengthening the strategic role of pharmacies. Daffa Farma Pharmacy still uses manual inventory management, which creates various challenges such as data inaccuracy, reporting delays, and inefficiencies in decision-making. This study aims to design a website-based inventory management application that can facilitate more accurate, efficient, and structured stock management. Data collection methods include observation, documentation, and interviews, using descriptive analysis techniques. The result of this study is a